FOOD AND FEEDING OF THE POST-LARVAE AND JUVENILES OF MEGALOPS CYPRINOIDES (BROUSS.) - Noble, A (Indian Journal of Fisheries, 2011)
Post-larvae of Megalops cyprinoides collected from the inshore area off Karwar were reared ia the laboratory into juveniles. They were fed in the laboratory with live plankton and their food and feeding were noted. They ate only the zooplankton and distinguished the edible from the non-edible, the big from the small and the live from the dead.